Testicular epidermoid cyst - Basri Çakiroglu; Nurettin Cem Sönmez; Orhun Sinanoğlu; Lora Ateş; Süleyman Hilmi Aksoy; Faruk Özcan (Wolters Kluwer Medknow Publications, 2015)
Epidermoid cyst of the testis is a benign, non-teratomatous tumour. It is often possible to make the diagnosis pre-operatively, combining typical sonographic features with normal biochemical tumour markers. The accurate pre-operative diagnosis will allow for testis-sparing surgery and prevent unnecessary orchiectomy. An 11-year-old boy with testicular epidermoid cyst who presented with pain in testis was presented in this report.